A six-year study of leiomyomata with emphasis on lipoleiomyoma - Manjula, C. P.; Simon, Naina Mary; Venkatesh, Kusuma; Muneer, Fazeela; Hemalata, M.; R., Rangaswamy (International Journal of Research in Medical Sciences, 2018)
Background: Leiomyoma is the most common benign neoplasm of the uterus. Lipoleiomyoma is a rare variant usually affecting women in the postmenopausal age group. Incidence of lipoleiomyoma varies from 0.59% - 2.1%. This study was undertaken to analyse the different variants, degenerative changes and to determine the incidence, clinical and morphological features of lipoleiomyoma amongst all the leiomyomas studied. Methods: This study was done in the Department of Pathology over a period of 6 years. Authors studied 575 patients with leiomyoma constituting a total of 1122 leiomyomata as some patients presented with multiple leiomyomata. Further clinicopathological correlation was done. Results: In the present study 98.03% of leiomyomata were uterine in location, 1.06% were cervical, 0.62% were in broad ligament and 0.26 % were in ovary. Among the 1122 leiomyomata studied, degenerative changes were noted in 19.6% of which hyaline degeneration was the most common. Leiomyoma variants constituted 5.27% of all leiomyomata. The incidence of lipoleiomyoma was 0.71% with size ranging from 3-10cm. Conclusions: Leiomyoma is a common tumor of the uterus and lipoleiomyoma variant is very uncommon with unknown etiology. They occur in postmenopausal as well as reproductive age group. The site of lipoleiomyoma can be uterine or extrauterine location such as broad ligament. Coexistance of metabolic derangement is an observation that may have a role in development of lipoleiomyoma.